KENONG GOYANG: SUATU KAJIAN GARAP MUSIKAL DALAM KARAWITAN GAYA SURAKARTA - Nur Sholikhah; Djoko Purwanto; Prasadiyanto Prasadiyanto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
The research entitled "Kenong Goyang: A Study on Musical Work in Surakarta Style Karawitan" is a type of qualitative research using an analytical descriptive approach. This study refers to the musical aspect of traditional Javanese music, namely karawitan. This research aims to explain and investigate musical garap as well as the formation factors of garap kenong goyang by using the garap theory from Rahayu Supanggah. While the formation factor of working on kenong goyang caused by the arrangement of the balungan and working on the instrumen kendang as well as other supporting factors such as the form of the cultivator's gending and style. Based on written evidence, working on kenong goyang only occurs in the ladrang form of gending, namely, ladrang Sobrang pelog barang, ladrang Surung Dayung pelog nem, ladrang Kuwung pelog barang and ladrang Lengker pelog nem. However, in accordance with the development of work, kenonggoyang can also be served or worked into the slendro tuning system. With a note the shape and name of the gending is the same as the classification of the gending in the pelog tuning system which is adjusted to the balungan arrangement.  Kenong goyang is free or loose. This means that it can be served using kenong goyang or not, it depends on the gending treatment.